Analyzing the Impact of Side Friction on Vehicle Operating Costs and Urban Traffic Performance - Muthmainnah Muthmainnah; Nura Usrina; Nanda Savira Ersa; Gofirli Saumah (Journal of International Conference Proceedings, 2025)
On-street parking activities along Merdeka Barat Street in Lhokseumawe City have disrupted traffic flow. This study aims to determine the magnitude of Vehicle Operating Costs (VOC) resulting from on-street parking activities and to compare the VOC with parking fees (retributions). The study was conducted over a 7-day period, from 07:00 to 19:00 WIB. Traffic and parking characteristics were analyzed using the 2023 PKJI method, the VOC analysis employed the 2005 method from the Department of Public Works, and parking retribution was calculated based on Lhokseumawe City Qanun No. 1 of 2024. The analysis revealed that the highest average traffic volume occurred on Tuesday with 1,328 PCU/hour and a Level of Service (LOS) of D. The highest volume of light vehicle parking occurred on Wednesday, totaling 469 vehicles. The average vehicle speeds on Merdeka Barat Street were 51.92 km/h for motorcycles, 29.02 km/h for light vehicles, and 19.26 km/h for heavy vehicles. The total Vehicle Operating Cost (VOC) on Merdeka Barat Street amounted to Rp 21,305,163.94, while the total parking retribution reached Rp 6,164,000. The comparison between the VOC and parking retribution over the 12-hour observation period showed a significant difference of Rp 15,141,239.31.